2022
DOI: 10.1111/1462-2920.16138
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the microbial community of Cacopsylla spp. as potential factor in vector competence of phytoplasma

Abstract: Phytoplasmas are obligatory intracellular bacteria that colonize the phloem of many plant species and cause hundreds of plant diseases worldwide. In nature, phytoplasmas are primarily transmitted by hemipteran vectors. While all phloem‐feeding insects could in principle transmit phytoplasmas, only a limited number of species have been confirmed as vectors. Knowledge about factors that might determine the vector capacity is currently scarce. Here, we characterized the microbiomes of vector and non‐vector specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 112 publications
0
19
0
Order By: Relevance
“…A maximum likelihood phylogenetic analysis of these ASVs and 16S rRNA sequences from other psyllid‐associated endosymbionts showed that Group 1 pyri and Group 1 pyricola formed a strongly supported clade together with the endosymbiont of Cacopsylla jukyungi (BS = 97), which was well‐supported as a sister clade to the endosymbionts of C. myrthi and Anomoneura mori (BS = 100) (Figure 3B ). Likewise, the close relationship with Enterobacteriaceae endosymbionts in C. myrthi and A. mori had been observed also in other Cacopsylla species (Morrow et al, 2020 ; Schuler et al, 2022 ), suggesting that these ASVs represent an endosymbiont clade widespread in the subfamily of Psyllinae (Psyllidae). In contrast, the most abundant ASVs assigned to Enterobacteriaceae in C. pyrisuga were referred to as “Group2 pyrisuga ” in our study (87.56% of all reads from C. pyrisuga ).…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…A maximum likelihood phylogenetic analysis of these ASVs and 16S rRNA sequences from other psyllid‐associated endosymbionts showed that Group 1 pyri and Group 1 pyricola formed a strongly supported clade together with the endosymbiont of Cacopsylla jukyungi (BS = 97), which was well‐supported as a sister clade to the endosymbionts of C. myrthi and Anomoneura mori (BS = 100) (Figure 3B ). Likewise, the close relationship with Enterobacteriaceae endosymbionts in C. myrthi and A. mori had been observed also in other Cacopsylla species (Morrow et al, 2020 ; Schuler et al, 2022 ), suggesting that these ASVs represent an endosymbiont clade widespread in the subfamily of Psyllinae (Psyllidae). In contrast, the most abundant ASVs assigned to Enterobacteriaceae in C. pyrisuga were referred to as “Group2 pyrisuga ” in our study (87.56% of all reads from C. pyrisuga ).…”
Section: Resultsmentioning
confidence: 65%
“…These endosymbionts were recovered at a very high relative abundance and were identified as unclassified Enterobacteriaceae that are not yet formally described. Similarly, Morrow et al (2017Morrow et al ( , 2020, Kwak et al (2021), Nakabachi et al (2022) and Schuler et al, 2022 found endosymbionts referred to as unclassified Enterobacteriaceae in several Cacopsylla species. Altogether, unclassified Enterobacteriaceae were detected in six out of seven currently recognized psyllid families (cf.…”
Section: Potential Co-primary Endosymbionts Of Pear Psyllids and Thei...mentioning
confidence: 90%
See 2 more Smart Citations
“…The opposite was true for the non-infected individuals of C. picta, which harbored a lower number of bacterial taxa compared to the infected individuals. Psyllids with a high phytoplasma concentration had more divergent microbiomes and, most importantly, there was a signi cant difference between the microbiomes of C. melanoneura, C. picta and eight non-AP transmitting Cacopsylla species, highlighting the potential role of the microbiome in the acquisition and transmission of phytoplasmas (Schuler et al 2022). Therefore, further studies should be performed on the microbiome of C. melanoneura from NW and its potential interaction with 'Ca.…”
Section: Discussionmentioning
confidence: 99%